Deconstruction of the Existence of Khidr: A Study of Sheikh Mahfudz al-Tarmasi’s Thought Through Derridean Hermeneutics Approach - Agil, Muhammad; Alwi, Alwi Shobri; Mahmudi, Mahmudi (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
Discussions on the existence of Prophet Khidr in Islamic tradition have long been debated. Questions about his status as a prophet or saint, whether he is still alive or has passed away, and other issues remain significant among Muslims. These debates have also drawn the interest of Sheikh Mahfudz al-Tarmasi, a prominent Nusantara scholar. In his work, “Ināyat al-Muftaqir bimā Yata`allaq bi Sayyidinā al-Khidr `Alaihi al-Salām.” al-Tarmasi offers detailed and critical insights into Prophet Khidr’s existence. This research examines al-Tarmasi views using Derridean hermeneutics to deconstruct traditional thoughts on Prophet Khidr and encourage new interpretations. Employing a qualitative descriptive literature method, the study aims to gain a deeper understanding of Prophet Khidr’s existence. By applying Derrida’s deconstructive approach, this paper shows how al-Tarmasi addresses the contradictions among the views of Sufis, hadith scholars, and jurists about Prophet Khidr. The findings suggest that al-Tarmasi supports the idea that Prophet Khidr is still alive, thus reinforcing the Sufi perspective in Islamic tradition. This alignment not only highlights al-Tarmasi’s critical stance but also contributes to the broader discourse on the diverse interpretations of Islamic teachings.